Intelligent configuration of social support networks around depressed persons - Ab. Aziz, Azizi; Klein, Michel C. A.; Treur, Jan (Springer Berlin Heidelberg, 2011)
Helping someone who is depressed can be very important to the depressed person.A number of supportive family members or friends can often make a big difference.This paper addresses how a social support network can be formed, taking the needs of the support recipient and the possibilities of the potential support providers into account.To do so, dynamic models about the preferences and needs of both support providers and support recipients are exploited. The outcome of this is used as input for a configuration process of a support network. In a case study, it is show how such an intelligently formed network results in a reduced long term stress level.